2002
DOI: 10.1291/hypres.25.303
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cardioprotective Agent, JTV-519, Is Abolished by Nitric Oxide Synthase Inhibitor on Myocardial Metabolism in Ischemia-Reperfused Rabbit Hearts

Abstract: We investigated the effect of a novel cardioprotective agent, JTV-519, with or without a nitric oxide synthase inhibitor, L-NAME, on the myocardial metabolism and contraction during ischemia and reperfusion by means of phosphorus 31-nuclear magnetic resonance ( lated compounds during the ischemic period, could be blamed. Nonetheless, even in cases in which ATP does not decrease and creatine phosphate recovers rapidly after short periods of ischemia, stunning is already present. The fact that the stunned myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The events in the transition from ischemia to infarction are very complex and cannot simply be ascribed to a depletion of ATP (13,14). Rather, the depletion of ATP should be seen as a marker of 1) the severity of the ischemic process; 2) a depressed rate of anaerobic glycolysis in severely ischemic tissue that is caused by an accumulation of glycolytic end-products; 3) an inhibited lipid metabolism with an accumulation of intermediates such as acylcoenzyme A (acyl CoA) and acyl carnitine, with an inhibition of mitochondrial metabolism; and 4) an accumulation of intercellular calcium with ischemic contracture and the utilization of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…The events in the transition from ischemia to infarction are very complex and cannot simply be ascribed to a depletion of ATP (13,14). Rather, the depletion of ATP should be seen as a marker of 1) the severity of the ischemic process; 2) a depressed rate of anaerobic glycolysis in severely ischemic tissue that is caused by an accumulation of glycolytic end-products; 3) an inhibited lipid metabolism with an accumulation of intermediates such as acylcoenzyme A (acyl CoA) and acyl carnitine, with an inhibition of mitochondrial metabolism; and 4) an accumulation of intercellular calcium with ischemic contracture and the utilization of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…The events in the transition from ischemia to infarction are very complex and cannot simply be related to the depletion of ATP [26,27]. Rather, the depletion of ATP should be seen as a marker of (1) the severity of the ischemic process, (2) a depressed rate of anaerobic glycolysis in severely ischemic tissue, which is caused by an accumulation of glycolytic end products, (3) an inhibited lipid metabolism with an accumulation of intermediates such as acyl CoA and acyl carnitine, with an inhibition of mitochondrial metabolism, and (4) an accumulation of intercellular calcium with ischemic contracture and the utilization of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…The drug has been reported to have a very strong antiarrhythmic effect by reversing atrial fibrillation in a canine sterile pericarditis model [16]. It has also been reported that the drug exhibits significant potential for improving myocardial relaxation during ischemia, accompanied by the inhibition of the decrease in the cellular ATP level [13]. The involvement of FKBP 12.6 (FK-506 binding protein, calstabin2) suggested the importance of the calcium handling system in these cardioprotective effects [31,32].…”
Section: Introductionmentioning
confidence: 99%